Revitalizing the Dawan language: Community-based and technological approaches to language preservation - Isu, Rudolof Jibrael (TALENTA, 2025)
The Dawan language (Uab Meto), spoken by the Atoin Meto people in western Timor, Indonesia, is facing serious endangerment due to both internal and external pressures. Intergenerational transmission is weakening, youth attitudes toward the language are increasingly hostile, and the dominance of Indonesian and foreign languages in education, governance, religion, and media further marginalizes its use in daily life. The influence of urbanization, migration, and economic modernization also contributes to language shift and erosion of traditional linguistic domains. This literature-based study explores the multidimensional and intersecting challenges contributing to the declining vitality of Dawan and offers a strategic, community-centered framework for its revitalization. The novelty of this study lies in its integrative and interdisciplinary approach, combining language ecology theory, functional bilingualism, and digital innovation grounded in active community participation. It highlights the underexplored synergy between traditional institutions (such as customs councils and elders), higher education institutions, and community-led technological initiatives in safeguarding endangered languages. Through a critical analysis of existing literature, field reports, and language policy reviews, the study proposes a revitalization model that emphasizes the pivotal roles of local curriculum development, religious and customary institutions, digital storytelling, and the systematic digitization and archiving of linguistic and cultural knowledge. It also underscores the importance of collaboration between local governments, NGOs, and academic researchers in implementing sustainable language planning. Ultimately, the study aims to inspire further empirical, participatory, and interdisciplinary research into the preservation and revitalization of minority languages in Indonesia, particularly in the eastern archipelago, where such efforts remain scarce and fragmented.